2021
DOI: 10.3389/fpsyg.2021.643069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Interval Training and Moderate-Intensity Training on Stress, Depression, Anxiety, and Resilience in Healthy Adults During Coronavirus Disease 2019 Confinement: A Randomized Controlled Trial

Abstract: Objective: This study aimed to compare the effects of two intervention programs, (1) high-intensity interval training (HIIT) and (2) moderate-intensity training (MIT), on anxiety, depression, stress, and resilience during the confinement caused by the coronavirus disease 2019 (COVID-19) in healthy adults.Methods: A total of 67 adults who participated were randomly assigned to two groups: HIIT and MIT groups. The MIT group had to perform a home-based intervention based on aerobic exercises, whereas the HIIT gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 59 publications
11
53
0
Order By: Relevance
“…This is consistent with previous findings that show that high-intensity exercise at 90% HRmax more effectively reduces body fat mass and visceral fat mass, compared with moderate-intensity continuous cycling in obese men and women [26], additionally, HIIT is more effective on protein synthesis and lipid metabolism than MICT [28]. Borrega et al (2021) reported that HIIT is a highly effective and time-efficient weight control strategy for busy people in modern society [30]. Moreover, a combined aerobic and anaerobic training program online was reported to unarguably alleviate metabolic disorders, including diabetes mellitus, and participation in HIIT for 75 min a week…”
Section: Effects Of Online Hiit On Body Composition and Abdominal Obe...supporting
confidence: 91%
“…This is consistent with previous findings that show that high-intensity exercise at 90% HRmax more effectively reduces body fat mass and visceral fat mass, compared with moderate-intensity continuous cycling in obese men and women [26], additionally, HIIT is more effective on protein synthesis and lipid metabolism than MICT [28]. Borrega et al (2021) reported that HIIT is a highly effective and time-efficient weight control strategy for busy people in modern society [30]. Moreover, a combined aerobic and anaerobic training program online was reported to unarguably alleviate metabolic disorders, including diabetes mellitus, and participation in HIIT for 75 min a week…”
Section: Effects Of Online Hiit On Body Composition and Abdominal Obe...supporting
confidence: 91%
“…People with high levels of physical exercise are more likely to develop resilience 49 . Further, individuals who maintained regular physical exercise during confinement reported significantly high levels of resilience 50 , 51 . Consequently, physical exercise could alleviate anxiety and depression by improving the level of resilience among college students during the COVID-19 epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that resilience-fostering measures could help to decrease psychological distress and loneliness. Thus, targeted interventions such as resilience training focussing on mindfulness and cognitive behavioral skills ( 87 ) as well as physical exercise ( 88 ) with a focus on outdoor activity could be recommended. Other measures such as reactivating the social network, e.g., through social media ( 89 ), or more frequent phone calls to family members and other related people could increase positive feelings and decrease the level of worry, possibly leading to higher resilience and subsequently to lower psychological distress and loneliness.…”
Section: Discussionmentioning
confidence: 99%